2011
DOI: 10.1038/cdd.2011.107
|View full text |Cite
|
Sign up to set email alerts
|

The executioners sing a new song: killer caspases activate microglia

Abstract: Activation of microglia and inflammation-mediated neurotoxicity are suggested to have key roles in the pathogenesis of several neurodegenerative disorders. We recently published an article in Nature revealing an unexpected role for executioner caspases in the microglia activation process. We showed that caspases 8 and 3/7, commonly known to have executioner roles for apoptosis, can promote microglia activation in the absence of death. We found these caspases to be activated in microglia of PD and AD subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 117 publications
(133 reference statements)
0
44
0
Order By: Relevance
“…We have reported the involvement of Toll like receptor 4 (TLR4) in hypoxic microglia activation both in vitro and in hypoxic neonatal rats [8]. In this connection, a novel role of TLR4-dependent caspase-3 activation has recently been reported in activated microglia after stimulation with lipopolysaccharide (LPS) [9, 10]. It was reported that TLR4-dependent caspase3 activation could promote microglia activation in the absence of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the involvement of Toll like receptor 4 (TLR4) in hypoxic microglia activation both in vitro and in hypoxic neonatal rats [8]. In this connection, a novel role of TLR4-dependent caspase-3 activation has recently been reported in activated microglia after stimulation with lipopolysaccharide (LPS) [9, 10]. It was reported that TLR4-dependent caspase3 activation could promote microglia activation in the absence of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence indicates that many of these so-called apoptotic caspases also exert nonapoptotic functions (for a review, see Hyman and Yuan [40 ]and Venero et al [41]). Similarly, typical ‘nonapoptotic' members such as caspases-1, -4 and -5 are proposed to induce ‘pyroptosis', a form of death associated with massive activation of inflammatory cells (for a review, see Labbe and Saleh [42]).…”
Section: Different Playing Fields: Classification Of Caspasesmentioning
confidence: 99%
“…Intranigral administration of DEVD-fluoromethyl ketone (fmk), a caspase-3 inhibitor, or rottlerin, a PKCδ inhibitor, mitigated LPS-induced expression of cytokines and proinflammatory molecules, therefore supporting the view that killer caspases play a significant role in the activation of microglia. Since unregulated response or overactivation of microglia can have disastrous neurotoxic consequences, especially to the dopaminergic system [41,100], we also tested the ability of intranigral administration of IETD-fmk, a caspase-8 inhibitor, to prevent microglia activation and preserve the integrity of the dopaminergic system in the MPTP-lesion mouse model of PD. We found that caspase-8 inhibition in vivo significantly reduced the density of activated microglia and promoted a modest but yet significant protection of the nigrostriatal dopaminergic system.…”
Section: Apoptotic Caspases: Versatile Players In Regulating Brain Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The apoptotic caspases are composed of initiator caspases, such as caspase-8, -9, and -10, and effector caspases, such as caspase-3, -6, and -7. 7,8 Effector caspases are responsible for cleaving various protein substrates, resulting in characteristic morphological changes and dismantling of the cell. 9 Caspases are synthesized as inactive zymogens, and effector caspases are activated following proteolysis by initiator caspases to separate the large and small subunits.…”
Section: Introductionmentioning
confidence: 99%